A Sequence in Subdomain 2 of DBL1a of Plasmodium falciparum Erythrocyte Membrane Protein 1 Induces Strain Transcending Antibodies (2013)
Immunity to severe malaria is the first level of immunity acquired to Plasmodium falciparum. Antibodies to the variant antigen PfEMP1 (P. falciparum erythrocyte membrane protein 1) present at the surface of the parasitized red blood cell (pRBC) confer protection by blocking microvascular sequestration. Here we have generated antibodies to peptide sequences of subdomain 2 of PfEMP1-DBL1a previously identified to be associated with severe or mild malaria. A set of sera generated to the amino acid sequence KLQTLTLHQVREYWWALNRKEVWKA, containing the motif ALNRKE, stained the live pRBC. 50% of parasites tested (7/14) were positive both in flow cytometry and immunofluorescence assays with live pRBCs including both laboratory strains and in vitro adapted clinical isolates. Antibodies that reacted selectively with the sequence REYWWALNRKEVWKA in a 15-mer peptide array of DBL1a-domains were also found to react with the pRBC surface. By utilizing a peptide array to map the binding properties of the elicited anti-DBL1a antibodies, the amino acids WxxNRx were found essential for antibody binding. Complementary experiments using 135 degenerate RDSM peptide sequences obtained from 93 Ugandan patient-isolates showed that antibody binding occurred when the amino acids WxLNRKE/D were present in the peptide. The data suggests that the ALNRKE sequence motif, associated with severe malaria, induces strain-transcending antibodies that react with the pRBC surface